Awareness of radiology staff in Saudi Arabia regarding patient privacy, ethical, and legal implications of sharing medical imaging on online platforms - Arif, Wejdan M. (Frontiers in Medicine, 2025)
BackgroundThe digitization of radiology through online platforms has introduced significant challenges in maintaining patient privacy and complying with ethical and legal standards, particularly in Saudi Arabia’s rapidly evolving healthcare system.AimTo assess the awareness levels of radiology professionals in Saudi Arabia regarding patient privacy, ethical responsibilities, and legal implications of sharing medical imaging on digital platforms.MethodsA cross-sectional survey was conducted among 293 radiology staff, including Radiologists and Radiologic Technologists, using a structured online questionnaire. Data were analyzed using descriptive statistics, t-tests, and ANOVA.ResultsParticipants demonstrated moderate awareness across all domains (mean scores ~3.1–3.2 on a 5-point scale). Radiologists reported significantly higher awareness than Technologists (p < 0.0001). Awareness also increased with years of experience and varied by region, with the Central region showing the highest scores.ConclusionDespite moderate overall awareness, significant disparities highlight the need for targeted training and policy reinforcement to ensure consistent compliance with privacy, ethical, and legal standards in digital radiology.